KNOWLEDGE AND PRACTICE ON PEST MANAGEMENT OF ETHNIC POTATO FARMERS IN SOUTHERN SHAN STATE, MYANMAR - Aung, Pyae Pa Pa; Visetnoi, Supawan (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2021)
Potato is cultivated as the main tuber crop which is essential for ethnic farmers’ household income in Southern Shan State, Myanmar. Most ethnic farmers use chemicals widely to enhance crop yield and reduce pests. Overuse and misuse of pesticides could lead to a series of health impacts and environmental issues. The main aim of the study is to explore farmers’ current practices and knowledge level on pesticides in potato production. The participants of 100 farmers were chosen from each village with a cluster and purposive sampling technique using structured questionnaires to collect the data from a village in Kalaw Township. The finding showed that 72% of farmers use only chemical pesticides due to more effective and received training from pesticide companies’ staff and whereas only 3% received information from governmental officials. Reasons to use alternative methods, types of alternative methods and where farmers learned alternative methods were significantly related to pest control methods. Farm experience in farmers was not associated with pest control methods. This study will help extension workers to provide appropriate training and improve farmers’ knowledge of pest control management for the highland crop.